Interventions to address mealtime support needs in dementia: A scoping review. - Lígia Passos; João Tavares; Melissa Batchelor; Daniela Figueiredo (PLoS ONE)
The decrease in cognitive and physical ability among people with dementia can significantly affect eating performance, resulting in mealtime support needs that could lead to inadequate oral intake, weight loss, malnutrition, and reduced functionality in activities of daily living. This scoping review aimed to identify and summarize available research literature on mealtime interventions for people with dementia, and their impact on older people with dementia living in a residential care setting, care staff, and care context/environment. A scoping review of available research published in English, French, Portuguese, or Spanish, was conducted according to the methodology established by The Joanna Briggs Institute. The search was conducted between November 2022 and February 2023 in the following databases: MEDLINE, Web of Science, Scopus, CINAHL Complete, and SciELO. A total of 275 articles were retrieved, of which 33 studies were selected according to inclusion criteria. The interventions were classified into four general categories: environmental, mealtime assistance, staff training, and multicomponent. Most studies demonstrated effectiveness in increasing oral intake and improving behaviors such as agitation and aggression in people with dementia. The impact of interventions on care staff was linked to greater knowledge and attitudes towards mealtime support needs. There is a lack of reporting on the impact of interventions on the care context/environment. Most interventions examined the effects exclusively on residents, focusing on their oral intake and behavioral patterns, particularly agitation among individuals with dementia. However, it is crucial to conduct studies that evaluate the impact on administrators, to comprehend the viewpoints of various hierarchical levels within an organization regarding challenges associated with mealtime. The findings of this scoping review can support the development of new supportive programs, or strategies to improve mealtime experience with positive impact according to the reality and needs of each person or institution.